2007
DOI: 10.1080/10398560601083068
|View full text |Cite
|
Sign up to set email alerts
|

The Green Card Clinic: Overview of a Brief Patient-Centred Intervention Following Deliberate Self-Harm

Abstract: The clinic achieved high rates of first session attendance. This may have been attributable to the use of a few specific strategies aimed at increasing compliance, such as the green card, next-day appointments and assertive follow-up of non-attenders. For repeat self-harmers, we advocate an approach aimed at 'lifestyle change' rather than based on current psychological stressors. The Green Card Clinic service, involving a range of interventions tailored to meet the multitude of presenting needs, appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Previous studies have suggested that an emphasis on contact and assertive followup (Hvid & Wang, 2009;Wilhelm, Finch, Kotze et al, 2007), home visits by a community nurse (van Heeringen, Jannes, Buylaert et al, 1995), and continuity of care (Moller, 1989) may be of benefit. Furthermore, brief interventions in the form of letters and postcards that facilitate and maintain contact between individuals and services and may have a role to play in the management of suicidal behavior (Carter, Clover, Whyte et al, 2005;Motto & Bostrom, 2001).…”
Section: Interpretation and Implicationsmentioning
confidence: 97%
“…Previous studies have suggested that an emphasis on contact and assertive followup (Hvid & Wang, 2009;Wilhelm, Finch, Kotze et al, 2007), home visits by a community nurse (van Heeringen, Jannes, Buylaert et al, 1995), and continuity of care (Moller, 1989) may be of benefit. Furthermore, brief interventions in the form of letters and postcards that facilitate and maintain contact between individuals and services and may have a role to play in the management of suicidal behavior (Carter, Clover, Whyte et al, 2005;Motto & Bostrom, 2001).…”
Section: Interpretation and Implicationsmentioning
confidence: 97%
“…This is important given the reports of increased mortality and morbidity from a range of natural causes (2,3) in people presenting to Emergency Departments with suicidality. It is also important given the association between increased suicidality and poorer lifestyle behaviours that was documented in our earlier study (34).…”
Section: Discussionmentioning
confidence: 83%
“…This study used data collected from patients who attended the GCC at St Vincent's Hospital. The details of the GCC are discussed more fully in previous papers (33)(34)(35). In summary, following presentation to the Emergency Department with suicidal behaviour or ideation, all patients receive routine medical and psychiatric assessments (by an emergency doctor and psychiatry registrar).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. Clinical pathways identified in the literature and assessed against the criteria of Kinsman et al 15 The first five pathways [25][26][27][28][29] were developed by British National Health Service (NHS) Trusts as a result of local clinical practice guidelines. The criteria of Kinsman et al 15 Ò Ò Ò Ò Ò Designed for young people in the local area, stops at the ED but gives some post-discharge resources Nurse-led pathway 30 Ò Ò Ò Ò Ò Ò Description of care pathway to provide a 'fast track' through the ED Hunter Area model for management of selfpoisoning 18 Ò Ò Ò Ò Ò Care pathway covers all age groups but is only for self-poisoning, not other forms of deliberate self-harm or suicidality more generally A Pathways specifically for children and young people.…”
Section: Where To Next?mentioning
confidence: 99%